Performance in the Wartime Archive: Michio Ito at the Alien Enemy Hearing Board - Riordan, Kevin (American Studies, 2017)
Several days after the bombing of Pearl Harbor, the Japanese dancer and choreographer Michio Ito was apprehended by the United States government. In the documents establishing his indefinite detention, the Alien Enemy Hearing Board found Ito to be “an artist of artistic temperament, striking appearance, fine manners, cultured, educated and capable of any and all sorts of propaganda, espionage and sabotage.” In this essay I interrogate this sentence’s grammatical choreography, the “and” that links art, culture, and education to propaganda, espionage, and sabotage. The story of Ito’s remarkable career has surfaced frequently in the fields of transnational modernism, dance and performance studies, and Asian American criticism, but the period of his incarceration has yet to be addressed. By examining the archival traces of his hearing, I show how the same “artistic temperament” that allows Ito to collaborate with W. B. Yeats and Martha Graham and to dance for heads of state leads to his incarceration as a threat to American national security. My purpose in restaging Ito’s makeshift trial is not to exonerate him but to examine the shared hermeneutics of law and art, to indicate how swiftly a performance of otherness in the American context can shift from exotic and interesting to dangerous and in need of discipline.